The curse of the campfire weenies : and other warped and creepy tales / 3. - Lubar, David (Weenies, 2008)
Thirty-five creepy stories about pigeons, ancient predators, Girl Scouts, and other terrifying things. Includes author's notes on how he got his ideas for these stories.